2011
DOI: 10.1021/ol200536h
|View full text |Cite
|
Sign up to set email alerts
|

Vicinal C-Functionalization of Alkenes. Pd/Light-Induced Multicomponent Coupling Reactions Leading to Functionalized Esters and Lactones

Abstract: Under photoirradiation conditions using a xenon light, and in the presence of PdCl(2)(PPh(3))(2) as a catalyst, four-component coupling reactions comprising of α-substituted iodoalkanes, alkenes, carbon monoxide, and alcohols proceeded smoothly to give functionalized esters in good yields. When alkenyl alcohols were used as acceptor alkenes, three-component coupling reactions accompanied by intramolecular esterification proceeded to give lactones in good yields. The present reaction system represents the vicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 42 publications
2
20
0
3
Order By: Relevance
“…For instance, addition of octyl iodide 85 onto CO in the presence of ethanol was shown to provide in 16 h the desired ester 94 in 87% yield (Scheme 14.22, (1)) [67]. When the Pd catalyst was omitted, 94 was obtained in only 50% yield after 50 h. With α-iodoester 4, the generated electrophilic radical can add to an electron-rich olefin to generate a new nucleophilic radical that is then trapped by carbon monoxide [68]. Diester 96 is finally produced in high yield (2).…”
Section: Metal-mediated Atom-transfer Radical Carbonylationmentioning
confidence: 99%
“…For instance, addition of octyl iodide 85 onto CO in the presence of ethanol was shown to provide in 16 h the desired ester 94 in 87% yield (Scheme 14.22, (1)) [67]. When the Pd catalyst was omitted, 94 was obtained in only 50% yield after 50 h. With α-iodoester 4, the generated electrophilic radical can add to an electron-rich olefin to generate a new nucleophilic radical that is then trapped by carbon monoxide [68]. Diester 96 is finally produced in high yield (2).…”
Section: Metal-mediated Atom-transfer Radical Carbonylationmentioning
confidence: 99%
“…Consequently, we reported a series of three-or four-component coupling reactions to afford a wide range of carboxylic acid derivatives. [16] Herein, we report the full scope of the Pd/hn-induced ATC reaction for primary, secondary, and tertiary alkyl iodides, which can provide useful synthetic methods to prepare a variety of carboxylic acid derivatives. Interestingly, more than two decades ago, Kubiak and co-workers reported that [ 6 ] 2 is an isolable Pd dimer that, under photoirradiation, is likely to produce a pair of Pd radicals.…”
Section: Introductionmentioning
confidence: 99%
“…7 As such an example, the reaction of α-substituted iodoalkanes, CO, and alkenyl alcohols gave good yields of functionalized lactones. 8 Interestingly, however, in a similar reaction using an alkenylamine, we found that the envisioned lactam was obtained only in a low yield, and the carbamoylacetate was formed as a principal product. This led us to investigate the carbonylation reaction, and herein we report a novel synthesis of carbamoylacetates by the three-component coupling reactions comprising α-iodoacetate, CO, and amines (Scheme 1, equation 2).…”
mentioning
confidence: 78%